Pembatasan Nilai Perkara Yang Dapat Diajukan Banding Dan Kasasi Untuk Mewujudkan Asas Peradilan Cepat Sederhana Biaya Ringan (Universitas Musamus, 2023)
Courts as a means that are widely used by citizens in resolving problems are of course expected to become institutions that can satisfy the desires and desires of citizens seeking justice. However, in practice in court, things are often found that are obstacles in the judicial system that are not effective and efficient, the resolution of cases takes years, the process is long, the law can be submitted for a long time starting from appeal, cassation and judicial review, after it has permanent legal force, The execution was again violated by verzet law. Apart from the long process and expensive costs, resolving disputes through litigation also causes an accumulation of cases in court. The adage that states that justice is fast, simple and low cost is felt to be ineffective for justice seekers in Indonesia. The aim of this research is to determine the role of the Supreme Court institution in realizing the principles of fast, simple and low-cost justice. Normative legal research was chosen as the type of research in this writing with secondary data consisting of primary and secondary legal materials being the scope of the type of data studied. The data collection tool used was a literature study and a legal political approach was used to analyze the data. Data analysis uses a deductive method which is then described qualitatively descriptively in the conclusion. The results of this research conclude that in order to reduce the buildup of civil cases at the Supreme Court, especially those with a certain (small) case value in order to realize the principle of fast, simple, low-cost justice, restrictions on legal remedies have been implemented in the form of laws, statutes, PERMA and SEMA, and the Supreme Court has made blueprint for limiting the value of cases that can be taken as cassation.